PHYTOCHEMICAL AND ANTIOXIDANT ACTIVITY OF POLYHERBAL HYDROETHANOLIC EXTRACT IN STREPTOZOTOCIN INDUCED Β-CELL DESTRUCTION IN RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
In the view of pathogenicity of diabetics, there are certain factors involved to produce oxidative stress over the pancreatic -cells, that may be due glucose toxicity or due to involvement of free radical mechanisms. So, possible protection of -cells against oxidative stress can be achieved by employing antioxidants rich herbs, which will not only acts as free radical scavengers and also for prevention of -cells from further damage in Streptozotocin induced Type 1 diabetic rats. Preliminary phytochemical investigation of the polyherbal hydroethanolic extract (PHHE) supports the presence of active constituents like alkaloids, glycosides, flavonoids, terpenoids, etc for whose the anti oxidant property was assessed by -carotene linoleate in vitro method of oxidation in TLC plate. To ascertain the antioxidant property in vivo, the enzyme level studies like SOD, CAT & GSH in liver and pancreas were made and also the deeper investigation of role of anti oxidants and possible protection over pancreatic -cells were observed.